THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT, NORMATIVE COMMITMENT AND TRUST ON LEADERSHIP ON EMPLOYEE PERFORMANCE - Furianiskurlina; Muhamamad Ali; Erina yunika hanis; Alfina Hida Saputri; Ratih Pratiwi; Angelita Villaruel (CV Putra Publisher, 2022)
This research proposed to analyze and examine the relationship between perceived organizational support, normative commitment and trust in leadership on employee performance. This research is a descriptive quantitative research. The population in this study are all PT kayu lapis Indonesia/ PT Mitra Care Indonesia employees, the sampling technique used in this research is sensus because the entire population of the study was used as sample. Data collecting method used is questionnaire method. Data obtained been analyzed with spss analitycal equipment tools. The results of the validity test table show from SPSS data that the variable X1 is organizational perception, variable X2 is normative commitment, X3 is leadership trust in employee performance, and variable Y Employee performance can be explained that the value of r> rtable based on a significant test of 0.05 means that the items mentioned above are valid. The leadership trust variable has a positive and significant effect on employee performance by showing the results of 0.057 and sig 0.469. It can be said that the better the trust in the leader, the higher the employee's performance.